Axis mundi - Valenti, Anne, author; Voss, Gary Wayne, advisor; Lundberg, Thomas R., committee member; Williams, Ron G., committee member; Silberberg-Peirce, Susan, committee member (Colorado State University. Libraries, 1991)
To view the abstract, please see the full text of the document.
Keywords: Symbolism in art; Symbolism (Psychology)